До питання локалізації першої в Україні тютюнової мануфактури у м. Охтирка - Берест, Ю.М. (Сіверщина в історії України, 2021)
У статті робиться спроба локалізації першої в Україні тютюнової мануфактури, яка діяла у м. Охтирка у першій половині ХVIII століття. Під час дослідження даного питання були використані як історичні, так і топонімічні, картографічні, ґрунтознавчі та археологічні джерела, що дало можливість більш точно визначити місце зародження першого центру тютюнового виробництва в Україні. The article attempts to localize the first tobacco manufactory in Ukraine, which operated in Okhtyrka in the first half of the 18th century. The process of creating a manufacturing industry began in Ukraine in the early modern times. One of such industrial facilities was the first tobacco manufactory in Ukraine, founded in Okhtyrka. The Russian King Peter I drew attention to the territory of Okhtyrka region as a possible place for growing tobacco from foreign seed material, and by his order the introduction of tobacco production began here in a short time. Okhtyrka Tobacco Manufactory began its activities in 1718 (19) and worked until 1759. In the memoirs of the Yakov Markovych, a specific place of growing and processing of Okhtyrka tobacco is mentioned – it is the city meadows. Directly related to tobacco production is a tract called «Manufactory», which residents identify with the area between the modern streets Mishechkina and Shyroka, near the bus station. This allows to more accurately determine the location of the tobacco factory in Okhtyrka. They are fully consistent with the localization of tobacco production in the tract «Manufactory» and information about the establishment of the Okhtyrka Tobacco Manufactory directly on one of the areas for grazing cattle on the outskirts of the city. The corresponding free territory can be found on the plan of Okhtyrka in 1787 in the southern part of the tract near Lake Moshenkove. The tobacco plantations themselves could stretch further in the south-eastern direction, because in this part of the city the more suitable for growing tobacco soils – Okhtyrka levadas – began. Outside the city, tobacco plantations may have continued from the eastern outskirts of Okhtyrka. Ceramic material of the 18th century originates from the territory in the Manufactory tract, which testifies to the lively economic activity in this area.